Liver transplantation for metastatic wild‐type gastrointestinal stromal tumor in the era of molecular targeted therapies: Report of a first case. Issue 10 (23rd April 2019) - Iesari, Samuele; Mocchegiani, Federico; Nicolini, Daniele; Benedetti Cacciaguerra, Andrea; Coletta, Martina; Montalti, Roberto; Mandolesi, Alessandra; Lerut, Jan; Vivarelli, Marco
Abstract : The gastrointestinal stromal tumor (GIST) is a digestive neoplasm of mesenchymal lineage. The treatment strategy for receptor tyrosine kinase‐mutated GISTs is well defined. Wild‐type GISTs (WT‐GISTs) respond unsatisfactorily to specific kinase inhibitors. Moreover, evidence shows that repeat surgery has limited benefit. We report the case of a young female patient who was diagnosed with liver metastatic WT‐GIST, after initial radical resection and adjuvant therapy with molecular targeted drugs. Due to the disease progression, a two‐stage surgery was performed, with the removal of extrahepatic lesions followed by a total hepatectomy. The patient is disease‐free after 4 years from liver transplantation (LT), performed under everolimus‐based immunosuppression. The treatment of WT‐GISTs remains a significant challenge due to the frequent resistance to tyrosine kinase inhibitors (TKIs). Liver transplantation might represent an effective treatment option for such disease. Abstract : A young female patient suffering from a liver‐only, recurrent wild‐type gastrointestinal stromal tumor, a condition commonly contraindicating surgery, undergoes successful liver transplantation and remains disease‐free after a long follow‐up, confirming the curative potential of liver transplantation for this indication.